რუსეთის არმიის დეზერტირები XVIII საუკუნის საქართველოში - თაბუაშვილი, აპოლონ; მარუაშვილი, თორნიკე (My University, 2019)
In the 18th century Georgia the Russian military corps was present in 1769-1772, 1783-1787 and 1796-1797. In 1770 soldiers of the Russian army were around 4000. As we know from the primary sources, the Russian soldiers frequently used to desert the army in this period. This was mainly caused by hardship and lack of discipline. During recalling the entire Russian corps from Georgia their remaining number was about 2000. Hence, as a result of military campaign the Russian corps lost almost 2000 soldiers. The part of those troops died in the battles, some others fall victim of various diseases, but large portion of troops simply deserted the army. The most of renegade soldiers remained in Georgia while few others could left Georgia and went to neighboring countries. New wave of the Russian deserters appeared in 1796-1797. Document materials demonstrate that the soldiers are deserting the Russian army in East Georgia. At that time several hundred militaries deserted the Russian corps. Erekle II king of Kartli and Kakheti helped and sheltered the renegade Russian soldiers. This was caused by following reason: as we know, in the 70s of 18th century field artillery was established in Georgia. Erekle II made a lot of efforts to create that artillery in Georgia. Artillery corps needed not only funds, but qualified artilleryman as well. King invited the Georgians from Russia and even sent some young Georgians to Russian Empire to study artillery. But the lack of qualified personnel was obvious. The Russian deserters were used to solve that problem. Documents confirm that the Russian deserters served in artillery corps of the Georgian army and similar to local militaries they also had salaries. The Georgian government had obligation to satisfy them with commodities, clothes and living spaces. Erekle's measures were against the interests of the Russian Empire, hence the Russian officials and even Emperor requested from Erekle to cease protection of the Russian deserters and they demanded to send those people back in Russia. Despite that Erekle always acted in accordance with his interests and ignored these demands.
DESERTERS OF THE RUSSIAN ARMY IN THE 18TH CENTURY GEORGIA
https://geohistory.humanities.tsu.ge/ge/procedings/83-shromebi/174-shromebi-15.html
Keywords: ტოტლებენი; სუხოტინი; დეზერტირები